Gonadotrophins: The future - Madhuri Patil (Wolters Kluwer Medknow Publications, 2014)
The role of the IVF clinician is to make the ART treatment safe, patient-friendly, cost effective and at the same time offer good and high quality treatment. IVF protocols are a burden for women and are one of the potential reasons why women don't return for subsequent cycles. Frequent injections may increase stress and also result in high error rates. Simple short treatment regimen with optimal recovery of good quality oocytes results in development of good quality embryos followed by SET in treatment and cryopreservation cycles are a less burden and result in related lesser discontinuation, side effects, treatment cycles in time and are more cost-effective. Development of FSH analogues with longer terminal t1/2 and slower absorption to peak serum levels will increase the efficiency, decrease the side effects and also is easy to administer. This makes it convenient for the patients increasing the compliance. A certain minimum LH concentration is necessary for adequate thecal cell function and subsequent oestradiol synthesis in the granulosa cells. Adjuvant r-HLH gives clinician's precise control over the dose of LH bioactivity administered to target the therapeutic window. New parenteral, transdermal, inhaled and oral fertility drugs and regimens are currently under research and development with the objective to further simplify treatment for ART.